2015
DOI: 10.1007/s00170-015-7333-6
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of incremental sheet forming based on GTN damage model

Abstract: An attempt was made to analyze the damage evolution and ductile fracture of incremental forming at the microscopic level. Firstly, an extended Gurson-TvergaardNeedleman (GTN) model integrating with Hill'48 anisotropic yield criterion was established and numerically implemented by User-defined Material Subroutine (VUMAT) in the commercial finite element software ABAQUS. Then, the VUMAT program was verified via a single element test, and its damage parameters were determined through the combination of the simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 36 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…(1)) is modified by introducing the Hill (1948) equivalent stress instead of the von Mises one (see, e.g., Chen and Butcher, 2013;Kami et al, 2015;Li et al, 2015). The corresponding expression of equivalent stress is given by…”
Section: Modeling Of Ductile Damagementioning
confidence: 99%
“…(1)) is modified by introducing the Hill (1948) equivalent stress instead of the von Mises one (see, e.g., Chen and Butcher, 2013;Kami et al, 2015;Li et al, 2015). The corresponding expression of equivalent stress is given by…”
Section: Modeling Of Ductile Damagementioning
confidence: 99%
“…Blaga and Oleksik [17] have tried 3 different forming paths to create a frustum of a cone using DC04 steel sheet and concluded that the spiral path is the best among used strategies due to the occurrence of homogenous distribution of strains. Similar spiral path was used in both experimentation and FEA to produce truncated cone in Stainless steel 304, DC06 and aluminum alloy AL5052 by Golabi and Khazaali [18], Li et al [19] and Wang et al [20]. Experiment and FEA was carried out by Neto et al [21] using circular path and found that stress and strain FEA results are in good agreement with experimental results.…”
Section: Introductionmentioning
confidence: 88%
“…Therefore, the plastic deformation of the material is caused by the deviatoric stress. It can be seen from Equation (7) that the deformation of the contact zone meets the condition of plane pure shear deformation. That is, the principal stresses in two opposite directions have the same size, and those in the other direction are null.…”
Section: Materials Deformation Analysismentioning
confidence: 99%
“…This new market demand can be met using digital incremental forming [1][2][3], which is a new sheet metal flexible rapid prototyping technology [4][5][6]. In contrast to the traditional stamping forming, this technology can produce sheet metal parts with large forming limits and complex shapes without the use of a special die, or by simply using model support, which makes it ideal for rapid prototyping and small batch production [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%